The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17061814
|View full text |Cite
|
Sign up to set email alerts
|

Committed to Health: Key Factors to Improve Users’ Online Engagement through Facebook

Abstract: Health organizations, continuously exposed to public scrutiny due to the social relevance of the services provided, have adopted social media to disseminate information about health but also about themselves, and thus, reducing uncertainty and improving communication. In this context, users’ participation in social media has become one of the main indicators of their effectiveness, highlighting the importance of analyzing which factors enhance online engagement. This research extends the number of variables id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
1
12
0
1
Order By: Relevance
“…Concerning the former, research has shown that a higher intensity of government communication via social media positively influences citizens’ adherence to preventive measures [ 55 ]. Previous crisis-related research indicates that health organisations rely more often on traditional media than social media when framing a health crisis [ 56 , 57 ]. In the context of Covid-19, recent research shows that the tweets of politicians generated the most attention, while those of celebrities attracted the most engagement overall, thereby indicating the value of personal versus official communication channels [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the former, research has shown that a higher intensity of government communication via social media positively influences citizens’ adherence to preventive measures [ 55 ]. Previous crisis-related research indicates that health organisations rely more often on traditional media than social media when framing a health crisis [ 56 , 57 ]. In the context of Covid-19, recent research shows that the tweets of politicians generated the most attention, while those of celebrities attracted the most engagement overall, thereby indicating the value of personal versus official communication channels [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that a higher intensity of government communication via social media positively in uences citizens' adherence to preventive measures (53). Previous crisis-related research indicates that health organisations rely more often on traditional media than social media when framing a health crisis (54,55). Our study results reveal that although dominated by individual voices ('in uencers' with many followers), both health/government institutions and the media also had a signi cant presence.…”
Section: Discussionmentioning
confidence: 51%
“…One of the main takeaways from these studies is that the message format affects the level of users’ web-based commitment to health organizations via social media [ 51 ]. Other studies (2/35, 6%) were tied to the assessment of the effectiveness of different types of posts on Facebook.…”
Section: Resultsmentioning
confidence: 99%